Pembuatan Makanan Ringan Produk Ekstrusi Dari Subgrade Ubi Jalar Goreng Beku Sebagai Bahan Substitusi Serta Analisis Kelayakan Finansial - Betha Ika Wilistien (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
The objective of this research is to determine the influential proportion of sweet potato Subgrade frozen usage as the substitution material toward the production of an extract product snack by using corn grits and rice. The parameters examined were organoleptic characteristic and proper analysis of financial. The organoleptic analysis comprises taste, crispiness, appearance, color, and aroma. The chemical analysis includes sucrose, water, and essence, as well as protein content. The result of this research shows that organoleptic testing toward the taste of an extract product snack by using Beni azzuma sweet potato subgrade indicates that the combination treatments give a positive influence toward organoleptic characteristics of the product. An extract product of snack product from Beni azzuma sweet potato Subgrade as the substitution material with 95% rice formula and 5% Beni azzuma sweet potato Subgrade is chosen as the best product for having the highest weight or quality, 0.970. Proper analysis from the snack processing is shown by NPV score, Rp. 2.,016,418,748 (bigger than zero), the IRR score is 50.00% (bigger than deposit interest, 12.56%). The investment expense needed for constructing the unit of an extract product snack processing with Beni azzuma sweet potato Subgrade as the substitution material is Rp. 330,978,230. The investment will be back after 3 years 5 months, and every year the project can give the profit of 50% from the investment expense.